The mechanism of telomere protection: a comparison between Drosophila and humans. - Cenci, G.; Ciapponi, L.; Gatti, M. (Chromosoma, 2005)
Drosophila telomeres are maintained by transposition of specialized retrotransposons rather than by telomerase activity, and their stability is independent of the sequence of DNA termini. Recent studies have identified several proteins that protect Drosophila telomeres from fusion events. These proteins include the telomere capping factors HP1/ORC-associated protein (HOAP) and heterochromatin protein 1 (HP1), the Rad50 and Mre11 DNA repair proteins that are required for HOAP and HP1 localization at telomeres, and the ATM kinase. Another telomere-protecting factor identified in Drosophila is UbcD1, a polypeptide highly homologous to class I ubiquitin-conjugating E2 enzymes. In addition, it has been shown that HP1 and both components of the Drosophila Ku70/80 heterodimer act as negative regulators of telomere length. Except for HOAP, all these proteins are conserved in humans and are associated with human telomeres. Collectively, these results indicate that Drosophila is an excellent model system for the analysis of the mechanisms of telomere maintenance. In past and current studies, 15 Drosophila genes have been identified that prevent telomeric fusion, and it has been estimated that the Drosophila genome contains at least 40 genes required for telomere protection. We believe that the molecular characterization of these genes will lead to identification of many novel human genes with roles in telomere maintenance.